Thanatophoric dysplasia- a case report - Olusoji Edward Jagun; Mojisola Adejoke Olusola-Bello; Abiodun Folashade Adekanmbi; Omodele Oluyemisi Jagun; Tolani Oduwole (The Pan African Medical Journal, 2020)

(untitled)
A case of thanatophoric dysplasia with sudden death at term is hereby presented. Thanatophoric dysplasia is an uncommon, lethal skeletal dysplasia which is associated with mutation in the extracellular region of fibroblast growth factor receptor 3 (FGFR3). It is an autosommal dominant condition that has sporadic occurrence and early ultrasound scan has not been of great benefit in its detection. Diagnosis is mostly made in the third trimester. The fetal death is usually due to severe respiratory insufficiency from a reduced thoracic capacity and hypoplastic lungs and/or respiratory failure due to brainstem compression. In view of the autosomal dominance of TD, it will be advisable for a woman with previous history to have prenatal screening to relieve parental anxiety and prevent late detection.